2004
DOI: 10.1038/sj.ejhg.5201255
|View full text |Cite
|
Sign up to set email alerts
|

Combining the transmission disequilibrium test and case–control methodology using generalized logistic regression

Abstract: To study the role of genetic factors in the etiology, susceptibility, or severity of disease, several methods are available. In a transmission disequilibrium test, genotypes of cases are compared to those of their parents to explore whether a specific allele, or marker, at a locus of interest appears to be transmitted in excess of what is expected on the basis of Mendelian inheritance. Such apparent excess transmission indicates that cases are being selected for that allele, thereby providing evidence that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
107
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(109 citation statements)
references
References 25 publications
0
107
0
2
Order By: Relevance
“…In this scenario, the entire sample for association mapping would consist of trios, unrelated controls, and perhaps unrelated cases. Nagelkerke et al (2004) proposed a joint analysis of such data using a likelihood-based approach, demonstrating that power is increased in comparison to methods that analyze trios and unrelated subjects separately. Epstein et al (2005) showed that power is improved after relaxing the assumption of parental mating-type distribution compared to the more general parental mating-type used by Nagelkerke et al (2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this scenario, the entire sample for association mapping would consist of trios, unrelated controls, and perhaps unrelated cases. Nagelkerke et al (2004) proposed a joint analysis of such data using a likelihood-based approach, demonstrating that power is increased in comparison to methods that analyze trios and unrelated subjects separately. Epstein et al (2005) showed that power is improved after relaxing the assumption of parental mating-type distribution compared to the more general parental mating-type used by Nagelkerke et al (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Nagelkerke et al (2004) proposed a joint analysis of such data using a likelihood-based approach, demonstrating that power is increased in comparison to methods that analyze trios and unrelated subjects separately. Epstein et al (2005) showed that power is improved after relaxing the assumption of parental mating-type distribution compared to the more general parental mating-type used by Nagelkerke et al (2004). In addition, they developed formal tests to determine whether data types can be combined, as well as for analyses of incomplete triad data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a TDT test, genotypes of cases are compared to those of their parents to explore whether a specific allele, or marker, at a locus of interest is transmitted to a greater degree than Mendelian inheritance would warrant. In order to integrate all available information and thereby increase the statistical power, Nagelkerke et al 5 proposed a new TDT statistic by combining a TDT test and a case -control result using the generalized logistic regression. For multiallelic markers, there are a number of extensions to the TDT after its debut.…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Nagelkerke et al [138] proposed a likelihoodbased association analysis of the data comprising of trio data, with unrelated controls, and possibly some unrelated cases. Nagelkerke et al [138] provided ad hoc procedures to determine whether trios and unrelated data can be safely combined.…”
Section: Combining Case-parent Trios and Unrelated Subjectsmentioning
confidence: 99%